2021
DOI: 10.1101/2021.10.26.465763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The glutathione import system satisfies the Staphylococcus aureus nutrient sulfur requirement and promotes interspecies competition

Abstract: Sulfur is an indispensable element for proliferation of bacterial pathogens. Prior studies indicated that the human pathogen, Staphylococcus aureus utilizes glutathione (GSH) as a source of nutrient sulfur; however, mechanisms of GSH acquisition are not defined. Here, we identify a previously uncharacterized five-gene locus comprising a putative ABC-transporter and γ–glutamyl transpeptidase (ggt) that promotes S. aureus proliferation in medium supplemented with either reduced or oxidized GSH (GSSG) as the sole… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Curiously, L-cysteine auxotrophies in other pathogenic bacterial species ( S. enterica and E. coli ) confer a fitness advantage to these bacteria in certain in vivo niches (47), suggesting that the same may be true in Lm . The pathogen Staphylococcus aureus is similarly partially auxotrophic for L-cysteine, lacking an intact sulfate assimilation pathway but can utilize limited inorganic sulfur sources like thiosulfate for growth, and recent work has highlighted the importance of L-cysteine acquisition mechanisms during infection (5153). Considering the essential role of L-cysteine for growth and virulence gene expression in Lm , it is compelling to suggest that partial L-cysteine auxotrophy is a pathoadaptive feature of Lm metabolism, representing an adaptation to a unique host environment.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, L-cysteine auxotrophies in other pathogenic bacterial species ( S. enterica and E. coli ) confer a fitness advantage to these bacteria in certain in vivo niches (47), suggesting that the same may be true in Lm . The pathogen Staphylococcus aureus is similarly partially auxotrophic for L-cysteine, lacking an intact sulfate assimilation pathway but can utilize limited inorganic sulfur sources like thiosulfate for growth, and recent work has highlighted the importance of L-cysteine acquisition mechanisms during infection (5153). Considering the essential role of L-cysteine for growth and virulence gene expression in Lm , it is compelling to suggest that partial L-cysteine auxotrophy is a pathoadaptive feature of Lm metabolism, representing an adaptation to a unique host environment.…”
Section: Discussionmentioning
confidence: 99%
“…The PSP system is a great use case to characterize using molecular evolution and phylogeny due to the variety of domain architectures, cellular localizations, and phyletic spreads of each of these protein families and operons. The PSP work, including this Lia operon use case, as well as other recent diverse biological applications [2][3][4][5][6][7][8][9][10][11] indicate that the MolEvolvR approach is invaluable in characterizing new protein families of interest in the context of evolution. Homolog data table with the best hits from all superkingdoms of life (queried across all RefSeq genomes).…”
Section: Phylogeny Finally We Usedmentioning
confidence: 97%
“…This gap impedes identifying and characterizing the complete molecular systems involved in various critical cellular processes such as molecular pathogenesis, antibiotic resistance, or stress response. Several studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] have demonstrated the power of molecular evolution and phylogenetic analysis in determining molecular functions of such proteins. There are many individual tools [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] for protein sequence similarity searches or ortholog detection, delineating co-occurring domains (domain architectures), and building multiple sequence alignments and phylogenetic trees.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, GSH has been reported to be a chemoattractant that entices bacteria to come in the close vicinity of Res_GSH@SNP and leads to cell disruption. 54 SEM images taken for the 2.5 × 2 cm 2 catheter piece showed less bacterial presence, which suggested that most of the bacteria died after the first contact with Res_GSH@SNP (Figure 8a−j). Bacterial cell migration was further supported by a bridge assay in which inoculated bacterial culture on one side of the plate (infection site) was supposed to migrate to the other side of the plate using a formed catheter bridge (2.5 × 1 cm 2 ; Figure 8k,l).…”
Section: Cell Viability Assaymentioning
confidence: 99%